Diuretic efficacy and phytochemical profiling of the 80% methanol extract of Sida schimperiana Hochst. ex A. Rich - Meharie, Birhanu Geta; Gashu, Dehnnet Abebe; Taye, Abebe Dagne; Alemie, Getinet Nibret; Bizuayehu, Getnet Tadege; Lulie, Yared Yibeltal; Tunta, Tewodros Agedew; Ejigu, Yenesew Wudu; Andualem, Abel; Kassa, Mekuanint Terefe (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Diuretics are used for edema, heart failure, and hypertension, but may cause side effects and resistance. Sida schimperiana is used for urinary retention in Ethiopian folk medicine, although its diuretic effects are unverified. This study aims to evaluate the diuretic potential and phytochemical content of the 80% methanol extract of S. schimperiana. Material and methods. Male rats were administered distilled water (2 mL/100 g), furosemide (10 mg/kg), or 80% methanol extract (100, 200, or 400 mg/kg). Diuretic effects were assessed by monitoring urination onset, urine volume, electrolyte levels, and pH. Phytochemical analysis was performed to explore underlying diuretic mechanisms. Results. The 80% methanol extract demonstrated significant diuretic and natriuretic effects in a dose- and time-dependent manner, surpassing the negative control. At doses of 200 and 400 mg/kg, diuresis (p<0.001) and sodium and chloride excretion (p<0.001) were notably increased at all time points. The treated group also showed significant changes in urine pH. Phytochemical analysis identified alkaloids, flavonoids, polyphenols, and tannins, with high concentrations of flavonoids (187.3 mg quercetin equivalent/g) and polyphenols (128.4 mg quercetin equivalent/g). Conclusion. This study affirmed the methanolic extract’s diuretic potency, comparable to furosemide, emphasizing its prospective therapeutic value.